Orientasi Local Wisdom dalam Kajian Filsafat Islam di Perguruan Tinggi Keagamaan Islam - Raden Lukman Fauroni (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2017)
The article scrutinizes the study of Islamic philosophy along with its dynamics within historical contexts. The dynamics of Islamic philosophy have been, among others, caused by the debate between proponents and opponents within the field. This article finds and demonstrates a new trend within the study of Islamic philosophy, which focuses on local wisdom. The Department of Aqidah and Filsafat Islam (AFI/Aqidah and Islamic Philosophy) of State Islamic University (UIN) Yogyakarta focuses on the integration of studies on philosophy, Islamic theology (kalām), and Sufism functionally as analytical tools in dealing with the contemporary problem of humanity. The Department of AFI of UIN Bandung puts emphasis on strengthening the Islamic philosophy, which is oriented to the development of Sundanese and Nusantara philosophy. Meanwhile, the Department of AFI of IAIN Surakarta addresses its study toward the Islamic philosophy to develop the philosophy of Java Islam. The dialogue and intense interaction with local wisdom will strengthen the Islamic philosophy and help it finds its momentum to offer applicative and appropriate solutions toward contemporary national and humanity problems. The Islamic philosophy based on local wisdom will also be able to eradicate the radical trans-national ideology.